Une Chaire dans une église XIIIe siècle
Slide from Boutelle's slide collection. Handwriting on frame of the physical slide says "from Beaux Arts records." On the righthand side of the image, there are the stamped words "UNIV. O CALIFORN" In the bottom corner of the image there is a signature that looks like "Aug. Royer," possibly Augustine Royer. Appears to be a drawing of a pulpit from the 13th century (Title in French: "Une Chaire dans une église XIIIe siècle")